Profil Kondisi Fisik Pemain Futsal Klub Brancos Kota Lubuklinggau - M Syroyyudin; Rais Firlando; Ever Sovensi (SJS: Silampari Journal Sport, 2021)
This study aims to determine the level of physical condition of futsal players at the Brancos Club, Lubuklinggau City. The method used is a survey. The sample is 20 people with the sampling technique using total sampling. Data collection in this study used 5 physical condition test items, namely (1) 6-second Sprint test for speed, (2) Illinois Agility Run test, (3) standing long jump test, (4) bleep test, (5) sit-up test. 60 seconds. The results of data analysis for the speed test (sprint) with an average value =